2017
DOI: 10.1021/acs.macromol.6b02754
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Hydrophobicity To Program Block Copolymer Assemblies from the Inside Out

Abstract: Hydrophobicity inherently affects a solutes behavior in water, yet how polymer chain hydrophobicity impacts aggregate morphology during solution self-assembly and reorganization is largely overlooked. As polymer and nanoparticle syntheses are easily achieved, the resultant nanoparticle architectures are usually attributed to chain topology and overall degree of polymerization, bypassing how the chains may interact with water during/after self-assembly to elicit morphology changes. Herein, we demonstrate how bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
180
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 64 publications
4
180
1
1
Order By: Relevance
“…While copolymerization of DAAM with DMA generates thermally responsive core‐forming copolymers, a] more recently it was reported that PDMA 30 ‐PDAAM x (60 ≤ x ≤ 90) lamellae exhibited a temperature‐induced postpolymerization morphological transition (Figure b) . The latter case is somewhat surprising given the insoluble nature of PDAAM.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
See 3 more Smart Citations
“…While copolymerization of DAAM with DMA generates thermally responsive core‐forming copolymers, a] more recently it was reported that PDMA 30 ‐PDAAM x (60 ≤ x ≤ 90) lamellae exhibited a temperature‐induced postpolymerization morphological transition (Figure b) . The latter case is somewhat surprising given the insoluble nature of PDAAM.…”
Section: Raft Aqueous Dispersion Pisamentioning
confidence: 99%
“…The effect of comonomer on PISA morphologies has been studied by several research groups. Zhang group introduced polar 4‐vinylpyridine (4VP) as a comonomer to adjust the solvophobic/solvophilic ratio of BCPs, thereby changing the morphologies in RAFT dispersion polymerization of nonpolar styrene (St) in methanol/water mixture . b] Similarly, Sumerlin group increased the degree of solvation of the core‐forming block by adding a more polar N , N ‐dimethylacrylamide (DMA) as a comonomer in RAFT aqueous dispersion polymerization of diacetone acrylamide (DAAM).…”
Section: Factors Affecting Bcp Nano‐object Morphologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…PISA is considered as an efficient and reliable strategy not only to produce amphiphilic diblock copolymers but also to prepare nanoobjects with controllable morphologies including spheres, worms, or vesicles in high yields and at high solid contents (typically 10–40 wt%) . It is nowadays well established that numerous parameters, mainly the monomer concentration, the chemical nature and the respective length of the blocks have an impact on the nanoobject morphology . Another important parameter that has been less considered in PISA so far is the macromolecular architecture .…”
Section: Introductionmentioning
confidence: 99%